2021
DOI: 10.20961/stjssa.v18i2.53615
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate characteristics and aggregate-associated soil organic carbon and carbohydrates of soils under contrasting tree land use

Abstract: <p><span>Protection of soil organic carbon and acid-hydrolyzable carbohydrates in aggregate-size fractions is important for appraising soil degradation and aggregation under land use types. Aggregate-associated soil organic carbon (SOC) and acid-hydrolyzable carbohydrates (R-CHO) in bulk soils and aggregate-size fractions of a sandy loam soil under Alchornea bush, Rubber, Oil palm and Teak plantations in southern Nigeria were studied. Results revealed significant differences in aggregate-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The increase in soil organic matter content as a result of organic inputs altered soil physical and chemical properties, which contributed to soil's productivity in terms of maize grain and biomass yield. Previous study reported that PM at the application rate of 15 Mg ha -1 increased maize grain yield of a sandy loam soil by 251% (Udom et al, 2019). Sharma et al (2019) also reported a significant increase in maize grain yield and biological yield following PM application.…”
Section: Assessment Of Maize Yield Parametersmentioning
confidence: 86%
“…The increase in soil organic matter content as a result of organic inputs altered soil physical and chemical properties, which contributed to soil's productivity in terms of maize grain and biomass yield. Previous study reported that PM at the application rate of 15 Mg ha -1 increased maize grain yield of a sandy loam soil by 251% (Udom et al, 2019). Sharma et al (2019) also reported a significant increase in maize grain yield and biological yield following PM application.…”
Section: Assessment Of Maize Yield Parametersmentioning
confidence: 86%
“…However, it could be concluded that the root density and soil management approaches may have resulted in higher organic C buildup in all land uses than the 5-year cassava cultivated land. Authors had suggested that land use changes can have a significant influence on SOC dynamics and carbon transport [26][27][28], and linked it to vegetative growth, root proliferation, organic matter breakdown, and subsequent organic matter retention in soil aggregates. The higher TN in forested and 5-year fallow soils might be attributed to the higher organic carbon, which came from the return of plant and root biomass as well as residues to the soil system [28] The C and N pool sizes varied significantly among land use types, with the forested soils storing greater C and N. However, sensitivity indices measured by CPI and NPI demonstrated that their susceptibility to change was comparable to total pools [17], and could be employed as a sensitive indicator for SOC and N changes.…”
Section: Discussionmentioning
confidence: 99%
“…Authors had suggested that land use changes can have a significant influence on SOC dynamics and carbon transport [26][27][28], and linked it to vegetative growth, root proliferation, organic matter breakdown, and subsequent organic matter retention in soil aggregates. The higher TN in forested and 5-year fallow soils might be attributed to the higher organic carbon, which came from the return of plant and root biomass as well as residues to the soil system [28] The C and N pool sizes varied significantly among land use types, with the forested soils storing greater C and N. However, sensitivity indices measured by CPI and NPI demonstrated that their susceptibility to change was comparable to total pools [17], and could be employed as a sensitive indicator for SOC and N changes. Although the TOC and TN decrease in depth, physical attributes of the soils such as clay content, soil bulk density, amount of macroand micro-pores may exert the protection of the carbon contained in the soil [29], leading to increases in carbon stocks in depth.…”
Section: Discussionmentioning
confidence: 99%